PENGARUH STRUKTUR KEPEMILIKAN TERHADAP KINERJA PERUSAHAAN (STUDI EMPIRIS PADA PERUSAHAAN LQ-45 2013-2015) - Henny Ritha (Aliansi : Jurnal Manajemen dan Bisnis, 2018)
This study is conducted to analyze the effect of Ownership Structure of LQ-45 firms’ performance. Both Ownership structure which is represented by Institutional Ownership, Managerial Ownership and Foreign Ownership are independend variables, with Retun On Equity is used as a proxy for performance valuation. This study used secondary data that consist of annual financial reports obtained from the Indonesia Stock Exchange for the period 2013 to 2015, and the number of the samples are consisting of 23 LQ-45 companies listed on the Indonesia Stock Exchange. The method used is a Multiple Linier Regression and hypothesis test namely model feasibility test (F test) and partial test (T-test). The research proves that managerial ownership has significant impact on firms LQ-45 performance, meanwhile institutional ownership and foreign ownership have no significant impact on firms LQ-45 performance. Simultaneously, the three variables have a significant effect and contributed 22.54 percent to the firm’s performance in Indonesian Stock Exchange from 2013 to 2015, meanwhile the remaining 77,46 percent is influenced by other variables. Researcher suggests prolonging the research period, extending the sample criteria and doing a qualitative study on investor behavior in investing.